2008
DOI: 10.1590/s1413-81232008000300022
|View full text |Cite|
|
Sign up to set email alerts
|

Source of funding and results of studies of health effects of mobile phone use: systematic review of experimental studies

Abstract: There is concern regarding the possible health effects of cellular telephone use. We conducted a systematic review of studies of controlled exposure to radiofrequency radiation with health-related outcomes (electroencephalogram, cognitive or cardiovascular function, hormone levels, symptoms, and subjective well-being). We searched Embase, Medline, and a specialist database in February 2005 and scrutinized reference lists from relevant publications. Data on the source of funding, study design, methodologic qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Studies supported by the pharmaceutical industry are well known to be much more likely to conclude that a drug is efficacious than studies conducted without such support, 22,23 but similar tendencies have been observed in other fields. [24][25][26][27][28] Gluttony is the related desire for an excess of anything, in our case mostly an inordinate appetite for credentials and publications. It involves preoccupation with producing and publishing to excess, thereby leading to social apathy.…”
Section: Lust Greed and Gluttonymentioning
confidence: 85%
“…Studies supported by the pharmaceutical industry are well known to be much more likely to conclude that a drug is efficacious than studies conducted without such support, 22,23 but similar tendencies have been observed in other fields. [24][25][26][27][28] Gluttony is the related desire for an excess of anything, in our case mostly an inordinate appetite for credentials and publications. It involves preoccupation with producing and publishing to excess, thereby leading to social apathy.…”
Section: Lust Greed and Gluttonymentioning
confidence: 85%
“…Many of the studies were financed by communications corporations so bias is inevitable. 59 studies were selected of which 12 of them were sponsored by the communications industry, 11 were sponsored by charity organizations, 14 received various sponsorships of which communications corporations took part and 22 had no specifications of funding sources [26] From the report, telecommunications firms had the highest number of funded studies so bias is very possible as their main goal is to remain in business. Odds ratio between charity organizations and telecommunications funded studies was 95% CI, 0.02-0.7829].…”
Section: Discussionmentioning
confidence: 99%
“…Other significant data have been published by Huss (Huss, Egger, Hug, Huwiler-Muntener, & Roosli, 2007), who selected particularly important articles about the biological and health effects of RF: if one is the average probability of s.s. positive results in work funded by public bodies, the probability of at least one positive result in those funded by the cellphone companies is just one positive result out of ten. The probability for studies with mixed funding sources lies somewhere between, and even studies not citing any source of funding (increasingly common owing to lax editorial work) are influenced to some extent.…”
Section: Box 1 Methodological Elements Needed To Ensure the Reliabilimentioning
confidence: 99%